Significance of the Scream: Otherness in Postcolonial and Gothic Fiction - Khair, Tabish (My University, 2014)
Starting with an examination of some of the gothic tropes used to narrate India in colonial literature (fiction and non-fiction), this paper will look at some highly visible postcolonial narratives of/about India and compare them to 19th century Gothic narratives. It will argue that the problem of narrating otherness can only be resolved partially – and in very different ways – by Gothic narratives and postcolonial ones. It will propose that the imperial Gothic sometimes manages to address aspects of colonial otherness that overtly postcolonial texts cannot access.
Born and educated in Bihar, India, Tabish Khair has won the All India Poetry Prize and published a number of critically acclaimed collections of poetry, including Where Parallel Lines Meet (2000) and Man of Glass (2010), and novels. His novels have been translated into various languages and short-listed for a dozen major awards, including the Man Asian Prize, the Encore Award and the Hindu Best Fiction Prize. He has also written or edited several ground-breaking studies and anthologies, including Babu Fictions: Alienation in Contemporary Indian English Novels (2001) and Other Routes: 1500 Years of African and Asian Travel Writing (2005). Apart from contributing to major academic and literary journals, he writes regularly for the Hindu in India and papers in UK. His latest novel is How to Fight Islamist Terror from the Missionary Position. Khair now lives in Denmark, where he is an Associate Professor at Aarhus University. Home page: http://www.tabishkhair.co.uk
Keywords: Novela india - S. XIX; Gothic; 19th century; India; Otherness; Postcolonial